Political culture: A concept that is usefully ambiguous - Landi, Oscar (1989)
One of the most important theoretical problems of the study of political cultures is to get out of the circularity that involves defining as political a discourse or cultural expression because it speaks of politics or is enunciated by a politician. The entrance of linguistic pragmatics as an instrument of analysis can move forward in this direction. From this point of view, a discourse or a cultural manifestation will not be political only because it "talks about politics" (semantic criterion), but because it performs certain types of transforming acts of intersubjective relations (syntactic and / or pragmatic criterion): it gives a place to "authorized" subjects (with "right to speak"), establishes "duties", builds "expectations", generates "trust".